Pendugaan Evapotranspirasi Pada Tanaman Padi Sawah di Kabupaten Bolaang Mongondow Utara Dengan Menggunakan Model Simulasi Neraca Air - Master R.L. Sirait; Johannes E.X. Rogi; Jeanne . Paulus; Selvie G. Tumbelaka (Universitas Sam Ratulangi, 2013)
ABSTRACTClimate is determining factor addition to rice production plant material and soil. Earthis currently experiencing climate change impact on reducing rice production. Drought is one ofthe effects of climate change due to water shortage conditions that accur within a specifiedperiod. This happens because the region received rainfall below average, North BolaangMongondow, an area of this research study is an area is sensitive to reduce rainfall, the dataindicate that the decline in productivity in the district due to rainfall. This study aims to estimateevapotranspiration in rice in the Northern Bolaang Mongondow districts using water balancemodel developed Handoko (1994). The conclusion that the model is able to predictevapotranspiration centers (Sangkub, Bintauna, Bolang Itang Timur, Bolang Itang Barat,Kaidipang dan Pinogaluman).Keywords: Climate, Evapotranspiration, simulation models, Productivity, Water Balance.